Effectiveness of Teacher Professional Development Programs in Church-Based Education Schools in Myanmar - Aung, Gum San; Nding, Nan Hkawn; Soliba, Bernadette Lamsis (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study investigated the effectiveness of Teacher Professional Development (TPD) programs in Church-Based Education (CBE) schools in Northern Shan State, Myanmar. This research primarily examined the impact and relevance of TPD programs on instructional quality and teacher performance, aiming to address contemporary challenges and the barriers to their implementation. This study employed a convergent parallel mixed-method design, with ten participants involved. The researchers integrated thematic analysis of the questionnaires and teacher interviews with descriptive survey analysis. The results highlighted that the existing TPD programs in the CBE context had a positive influence on teachers’ instructional practices and student learning outcomes, despite the challenges, such as resource limitations, financial constraints, a lack of contextual training, and restrictive governance. Thus, this study concluded that TPD programs must be tailored to the local context with adequate resource support to ensure sustainability and effectiveness. These findings provide practical implications for policymakers, educators, and teacher trainers to implement context-specific and well-resourced TPD initiatives in CBE schools to strengthen teachers’ professional growth.